Clinical Significance of Cerebrospinal Fluid Herpesvirus 6 Positivity- A Case Series Study - Burmester, Inês; Domingues, Rui M.; Freitas, Eduardo Ferreira; Regadas, Maria João; Cruz, André Santa (Archives of Clinical and Medical Case Reports, 2020)
Human herpesvirus 6 (HHV-6) is a common pathogen at childhood, remains in a latent form and can reactivate, causing encephalitis with the impairment of the immune system. The acute primary HHV-6 infection in adult immunocompetent hosts is being questioned. The cerebrospinal fluid (CSF) HHV-6 positivity can be detected in infection, in latency period, in asymptomatic reactivation or in viral chromosomic integration. To establish the clinical significance of CSF HHV-6 positivity, the authors reviewed the CSF HHV-6 positive cases in a tertiary hospital from 13 years. A total of 2111 tests were made with 0.9% of HHV-6 positivity. Only 2 cases were considered “likely” HHV-6 infected, reinforcing that most positive results do not indicate infection. Immune status and quantitative viral load studies on CSF and blood can be of great benefit, but clinical judgement is fundamental to determine the significance of HHV-6 positivity and need for treatment.